Multifunctional stratified composite coatings by electrophoretic deposition and RF co-sputtering for orthopaedic implants - Nawaz, Qaisar; Fastner, Steffen; Rehman, Muhammad Atiq Ur; Ferraris, Sara; Perero, Sergio; di Confiengo, G. Gautier; Yavuz, Emre; Ferraris, Monica; Boccaccini, Aldo R. (Journal of Materials Science, 2021)
In this study, multifunctional stratified antibacterial and bioactive coatings were deposited and characterised. Initially, PEEK/bioactive glass (BG)/ mesoporous bioactive glass nanoparticle (MBGN) layers with a thickness of 110–120 μm were deposited on stainless steel substrates using electrophoretic deposition (EPD). Thin silver nanocluster-silica composite layers with a thickness of 70–155 nm were then deposited by radio frequency (RF) co-sputtering on the previously deposited EPD coatings. The deposition was carried for two different sputtering times (20 min and 40 min), which led to different layer thicknesses. PEEK/BG/MBGNs coatings were also deposited via single-step EPD. A comparison between the physicomechanical and biological characteristics of single layer PEEK/BG/MBGNs composite coating and bilayer Ag-PEEK/BG/MBGNs is presented. Scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy (EDX) indicated that silver nanoclusters were homogeneously distributed in the multilayered EPD/RF coatings. An apatite-like structure was formed on the surface of the coatings upon immersion in simulated body fluid (SBF) after 1 day. Silver nanoclusters embedded in the silica matrix as a top layer provided controlled release of silver ions which led to a potent antibacterial effect against E. coli and S. carnosus. Single layer coatings exhibited a burst release of Ag ions, which led to antibacterial effects but were toxic to osteoblast cells. Finally, the results of WST-8 assays confirmed that the multi-structured coatings allow osteoblast-like cells to proliferate and attach strongly on the surface of the coatings.
CRIS-Team Scopus Importer:2021-02-12